2014
DOI: 10.1177/1468017314549709
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver strain, age, and psychological well-being of older spousal caregivers in Hong Kong

Abstract: Summary With the social policy movement, smaller family size, longer lifespan, confined living conditions, and limited caregiving resources, informal caregiving for older adults in Hong Kong has become the main responsibility of the spouse. Their psychological well-being becomes a major concern as they may experience immense strain from undertaking the caregiving role while suffering from age-related declines. To examine whether psychological well-being differs by caregiver strain and age, 112 spousal caregive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
0
19
0
2
Order By: Relevance
“…Studies were published between 2004 and 2015 and included 9487 participants (mean 410.1, range 57-1214). Five publications (including [23]) were Scandinavian [23][24][25][26][27], four came from the USA [28][29][30][31] with one each from Taiwan [32], Hong Kong [33] and Australia [34]. Again there were more female than male carer participants and where relationships were reported, carers were mostly spouses.…”
Section: Quantitative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were published between 2004 and 2015 and included 9487 participants (mean 410.1, range 57-1214). Five publications (including [23]) were Scandinavian [23][24][25][26][27], four came from the USA [28][29][30][31] with one each from Taiwan [32], Hong Kong [33] and Australia [34]. Again there were more female than male carer participants and where relationships were reported, carers were mostly spouses.…”
Section: Quantitative Studiesmentioning
confidence: 99%
“…The overwhelming aim in the quantitative studies was to investigate the negative consequences of caring on older people including depression, strain, burden and loneliness. Many investigated the relationships between carer demographic characteristics or the characteristics of those being cared for on these negative outcomes [25][26][27][28][29]33].…”
Section: Quantitative Studiesmentioning
confidence: 99%
“…Not surprisingly, family caregiving holds a myriad of ramifications for individual family members' health and well‐being (Camak, ; Grant, Cavanagh, & Yorke, ; Greenwood, Mackenzie, Cloud, & Wilson, ; Pinquart & Sorensen, ). Quantitative studies or reviews thereof have identified negative effects of family caregiving on caregiver health, including increased depression or mood disturbances, emotional distress, anxiety, physical exhaustion or decreased quality of life, and positive outcomes have also been reported, among them are personal growth, increased intimacy and a sense of meaning (Cassidy, ; Chow & Ho, ; Fletcher, Miaskowski, Given, & Schumacher, ; Greenwood, Mackenzie, Cloud, & Wilson, ; Hudson, ). In contrast, which family relationships or caregiving characteristics buffer against or put family carers at risk for adverse outcomes is less well understood (Alvira et al., ; Bastawrous, Gignac, Kapral, & Cameron, ; Hudson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos também mostraram que altos níveis de sobrecarga foram associados a baixos níveis de bem-estar 27,31,36,40 e afeto positivo. 44 E os menores com maior felicidade.…”
Section: Sobrecarga Do Cuidadorunclassified
“…Pruchno e Gitlin 52 afirmam que o cuidado afeta as pessoas de modo diferente de acordo com o tipo de atenção dispensada, a avaliação dos recursos existentes e em que estágio do desenvolvimento a pessoa se torna cuidadora. Alguns estudos dessa revisão 23,30,32,36,42 apontaram diferenças nas respostas de cuidadores de diferentes idades perante as demandas de cuidado, no entanto, elas precisam ser mais investigadas e precisamos saber como e porque elas ocorrem.…”
Section: Idade Do Cuidadorunclassified